Agricultural Transformation in Nepal - Joshi, Aabhas; Rawat, Ramesh (Nepalese Journal of Business, 2024)
This study examines the agricultural transformation in Nepal. Agricultural transformation is the dependent variable. The selected independent variables are technology adoption, climate change, government investments, land and property rights and gender. The primary source of data is used to assess the opinions of respondents regarding technology adoption, climate change, government investments, land and property rights and gender on agricultural transformation in Nepal. The study is based on primary data of 121 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of agricultural transformation in Nepal. The study showed a positive impact of technology adoption on agricultural transformation. It indicates that adoption of better technology in the agricultural sector will lead to better agricultural transformation. Similarly, the study showed a positive impact of climate change on agricultural transformation. It indicates that change in climate leads to better agricultural transformation. Likewise, the study revealed a positive impact of government investments on agricultural transformation. It indicates that proper and abundant investment by government leads to higher agricultural transformation. Further, the study observed a positive impact of land and property rights on agricultural transformation. It indicates that secured land and property rights and a proper managerial system lead to change in agricultural transformation. In addition, the study showed a positive impact of gender on agricultural transformation. It indicates that gender equality and equity on the agricultural sector the better will be the agricultural transformation.